Machine intelligence for chemical reaction space - Schwaller, Philippe; Vaucher, Alain C.; Laplaza, Ruben; Bunne, Charlotte; Krause, Andreas; Corminboeuf, Clemence; Laino, Teodoro (Wiley interdisciplinary reviews. Computational molecular science, 2022)
Discovering new reactions, optimizing their performance, and extending the synthetically accessible chemical space are critical drivers for major technological advances and more sustainable processes. The current wave of machine intelligence is revolutionizing all data‐rich disciplines. Machine intelligence has emerged as a potential game‐changer for chemical reaction space exploration and the synthesis of novel molecules and materials. Herein, we will address the recent development of data‐driven technologies for chemical reaction tasks, including forward reaction prediction, retrosynthesis, reaction optimization, catalysts design, inference of experimental procedures, and reaction classification. Accurate predictions of chemical reactivity are changing the R&D processes and, at the same time, promoting an accelerated discovery scheme both in academia and across chemical and pharmaceutical industries. This work will help to clarify the key contributions in the fields and the open challenges that remain to be addressed. This article is categorized under: Data Science > Artificial Intelligence/Machine Learning Data Science > Computer Algorithms and Programming Data Science > Chemoinformatics Machine intelligence has emerged in the chemical reaction space and enables chemists to accelerate the synthesis and discovery of novel molecules.